Diagnosing Herbicide Phytotoxicity in Citrus - Ramdas Kanissery; Nirmal Timilsina; Ruby Tiwari (EDIS, 2022)
Chemical weed control is an essential component of the ‘weed control toolbox’ for keeping the weeds checked in citrus groves. Citrus growers primarily rely on herbicides to manage weeds due to their efficacy and cost-effectiveness.  However, despite their benefits, herbicides may produce a wide range of unintended effects in citrus. For instance, an herbicide-related injury may occur due to improper spay practices, unfavorable weather conditions,  product misapplication, tank contamination, or herbicide carryover from the past application. Moreover, the movement of herbicides as a result of drift, volatilization or runoff, either on-site or from applications on adjoining areas, can also result in tree injury. This article discusses the diagnosis of such injuries from commonly used herbicides in citrus production.